Forming of communicative competence of future managers - Solodovnyk (Solodovnik) Tatyana O.; Sereda, Nataliia V.; Petrusheva, O. (Ассоциация открытой дипломатии, Грузия, 2018)
В тезисах рассмотрена педагогическая технология формирования коммуникативной компетентности будущих менеджеров.
Keywords: competence; communication; intercourse; communicative competence; managers; active methods of teaching; pedagogical technology; formation